Existing constructive solutions for flood protection (Международный научный журнал «Инженер», 2026)
Structural solutions for mudflow protection are technical and engineering solutions developed to protect structures from the negative consequences of mudflows, which mainly consist of a complex of measures implemented during the design, construction, and operation of structures. These solutions include special construction and technological methods to ensure infrastructure safety and minimize damage caused by mudflows. This article provides an analysis of existing methods for protecting bridge structures from mudflows. For the effective practical application of technical and technological measures to prevent the negative consequences of this mudflow threat, their adaptation to local conditions, along with world best practices in protecting against mudflow danger, a comparative analysis of local methods is of current importance.